Arterial Stiffness and Pulse Wave Velocity in Healthy People of Older Age Groups - Begum, Amina; Begum, Shelina; Arzu, Jahanara; Chowdhury, Md Rezaul Karim (Journal of Bangladesh Society of Physiologist, 2018)
Background: Arterial stiffness is associated with endothelial dysfunction. Increased arterial stiffness well correlates not only with coronary risk factors but also with age. Objective: To evaluate the arterial stiffness by assessing pulse wave velocity (PWV) in apparently healthy people of different age groups. Methods: This cross sectional study was conducted on of 60 apparently healthy subjects with 19-49(younger age) and 50-75 (older age) years of age. To calculate PWV, Carotido-femoral length and Transit Time, was measured by a measuring tape and Doppler respectively. For statistical analysis, Independent Sample ‘t’ test and Pearson’s correlation coefficient test was used. Results: In this study, PWV was significantly (p<0.001) higher in older age group. PWV of younger age group in both male and female were within normal range. But in older age group, 20% had abnormal PWV. Moreover, PWV was positively correlated with age & it was significant (p<0.001). Conclusion: From this study, it may be concluded that arterial stiffness may develop in apparently healthy elderly subjects and they are more prone to develop hypertension. J Bangladesh Soc Physiol. 2018, June; 13(1): 17-21